KARAKTERISTIK, MOTIVASI DAN NIAT BERKUNJUNG WISATAWAN MANCANEGARA KE DESA VISESA UBUD RESORT AND VILLA - I Made Surya Adi Dwi Negara; Luh Gede Leli Kusuma Dewi; I Putu Agus Wikanatha Sagita (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Desa Visesa Ubud Resort and Villa is a resort with a concept of returning to nature that provides various activities for tourists who stay. The purpose of this study was to determine the characteristics, motivation and intention of visiting foreign tourists to do activities in Visesa Village, Ubud Resort and Villa. The technique of determining the sample using purposive sampling with 100 respondents. The data analysis technique used in this study is the descriptive statistical technique. The results showed that the characteristics of foreign tourists who are active in the Village Visesa Ubud Resort and Villa are grouped into tourist descriptors and trip descriptors. The results of the motivation of foreign tourists who move in the Village of Visesa Ubud Resort and Villa based on the sub variable push factor motivation the results show that the highest driving factor is an indicator of leisure time. Based on the sub variable pull factor motivation, the results show that the highest pull factor is an indicator of amenities. The results of the variable intention to revisit tourists who are active in the Village Visesa Ubud Resort and Villa show that the highest indicator influencing tourist intentions is a complaining indicator or no complaints and overall agreed to visit the Village Visesa Ubud Resort and Villa as evidenced by tourists do not give criticism or complaints to the management or staff in Desa Visesa Ubud Resort and Villa.